Development of Learning Media using Powtoon Application on Liquid Pressure Topic - Rasid, R; Paramata, P; Yunginger, Y; Odja, O; Bouty, B; Setiawan, S (Jurnal Pendidikan Fisika Indonesia, 2022)
A valid, practical, and effective cartoon-based learning media on liquid pressure material has been developed by employing the Powtoon application and using Four-D (4D) stages. Expert validity and empirical validityof the media achieved an average score of 3.94 and 3.84 respectively with very valid criteria. The test instrument validity score was 3.37 with valid criteria. Supporting data for implementation is obtained using several instruments. The learning implementation observation sheet is used to observe teacher activity in the classroom; student responses were collected through questionnaires; and student activity is observed through the observation sheet. The practicality quality of teaching materials is obtained a percentage of 100% with very good criteria. The student responses to indicators of learning motivation with a percentage of 86.7%, indicators of ease and satisfaction of learning with a percentage of 84.7, learning innovation indicators with a percentage of 87.8%, and learning achievement indicators with a percentage of 89.2%. The effectiveness of the teaching material was obtained from observing student activities with a percentage of 86% in meeting I and of 88.7%% in meeting II. The student’s competency C2 (describing) achieve a percentage of 88.7%, C3 (applying) with a percentage of 81.75%, C4 (analyzing) with a percentage of 93.25%, and C5 (proving) with a percentage of 73%, all in good criteria. Learning outcomes in classical completeness obtains a percentage of 93.3%. It can be concluded that learning media in the form of teaching materials using the Powtoon application has the potential to increase students' understanding of concepts.